Effect of Red Nail Polish on Pulse Oximetry Reading - Hossain, Muhammad Sazzad; Rahman, Md Afzalur; Khatun, Rahena; Islam, Syed Ariful; Munira, Sanzida; Hasan, Mohammad IftaKhairul; Mandal, Muhammad Alamgir (KYAMC Journal, 2021)
Background: Pulse oximetry is a beat-to-beat, non-invasive and virtually risk-free method of assessing continuous arterial hemoglobin saturation. It is now a standard for monitoring care in the operating room and the post-anesthesia care unit. It is also widely used in the critical care setting. Numerous factors including dark skin, pigmentation, henna dye, nail polish etc. could lead to inaccuracy or ambiguous information about oxygen saturation. In many cultures, women decorate their fingernails with different colors of nail polish. Objectives: The purpose of this study was to determine the effect of red nail polish on the measurement of oxygen saturation. Materials and Methods: One hundred young women were recruited for this study and red nail polish was used to color the index finger of the non-dominant hand; the middle finger of the same hand was the control. Blood oxygen saturation was simultaneously measured by two calibrated pulse oximeters with two minutes interval for 30 minutes. Results: Red nail polish did not affect pulse oximetry measurement of oxygen saturation. There was no statistically significant difference between the control and the red nail polished fingers. Conclusion: Application of red nail polish does not cause statistically significant error in the measurement of oxygen saturation in young healthy individuals. KYAMC Journal Vol. 11, No.-4, January 2021, Page 181-183